Knowledge and practices among parents of asthmatic children: a quasi-experimental study conducted at tertiary care center of Western India - ., Dhirja; Sharma, Mukesh C.; Goyal, Jagdish P.; M., Remiya (International Journal Of Community Medicine And Public Health, 2021)
Background: Asthma is one of the most common chronic respiratory disease of childhood and emerging as a global health issue. It is primary cause of school absences and the third leading cause of hospitalization in children younger than the age of 15 years. Parents as the primary caregiver plays an important in management of the disease. The main objective of this study was to assess the knowledge and practices of parents of asthmatic children and improve it with the help of an informational booklet at AIIMS, Jodhpur. Methods: It was a quasi-experimental, pre-test post-test control group design on 60 parents of children suffering from asthma (30 in control group and 30 in experimental group) coming to paediatric OPD. Non probability purposive sampling was used to select the subjects. Self-structured tools like socio-demographic information, knowledge questionnaire and practices extended questionnaire were used to collect the required data. Reliability and validity of tools were analysed. Data analysis was performed in SPSS version 16. Results: The study findings reveal that most of the subjects had unsatisfactory level of knowledge and practices regarding asthma which significantly improvement in knowledge (t=11.449, p<0.05) and practices (t=-8.079, p<0.05) after application of informational booklet. Knowledge level of subjects were found to have significant association with education, occupation and monthly income of family. Conclusions: Prevention is better than cure. Parents are primary caregiver of children and spend most of the time with them. Their sufficient knowledge regarding asthma and right practices can help in reducing sudden asthma attacks and hospital visit in these children. Informational booklet have a positive impact on improving the knowledge and practices among parents.